The nuisance from industrial activities in Gebeng, Kuantan (a case study in taman balok makmur) - Norashima, Nawir (2015)
This thesis deals with the nuisance faced by the residents in Taman Balok Makmur, Kuantan. As we know that,Taman Balok Makmur is the nearest populated area to the Industrial Site in Gebeng, Kuantan. As there are rapid developments of construction activities, the people suffering discomfort nuisance in their daily routine. The road user had to content with the polluted road which is covered by the bauxite. The daily transportation come from the factory causing road pollution and damaged. This study was conducted to identify the types of nuisance and the factors contributing to nuisance which can cause discomfort feeling to the residents. The scope of this research is focusing on the residents in Taman Balok Makmur, Kuantan. The main methodology used for this study is survey questionnaire and observations. The study showed that the types of nuisance faced by the residents in Taman Balok Makmur is the lorries and other heavy transportation causing smoke, dust and dirt and also the bauxite and dirt covering the access road used by the residents while the most factors contributing to the nuisance in the area is the rapid development of construction.